2022
DOI: 10.1371/journal.pone.0277871
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of culture conditions for osteoclastogenesis in RAW264.7 cells

Abstract: Osteoclasts are the only multinucleated cells in vivo responsible for bone resorption and are vital for regulating bone remodeling and maintaining bone mass. The RAW264.7 cell line is widely used to study osteoclastic differentiation and biological molecular mechanism. However, protocols for inducing osteoclast formation in RAW264.7 cells vary considerably between laboratories, hindering the replication of results. Therefore, we tested the influence of culture conditions on osteoclast differentiation, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Treating RAW 264.7 cells with RANKL initiates osteoclast differentiation signaling through RANK, thereby inducing the expression of key differentiation-related genes, including c-Fos, NFATc1, OSCAR, DC-STAMP, cathepsin K, and TRAP [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, c-Fos and NFATc1 work synergistically to induce the expression of several key osteoclastogenesis-related genes [ 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treating RAW 264.7 cells with RANKL initiates osteoclast differentiation signaling through RANK, thereby inducing the expression of key differentiation-related genes, including c-Fos, NFATc1, OSCAR, DC-STAMP, cathepsin K, and TRAP [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Furthermore, c-Fos and NFATc1 work synergistically to induce the expression of several key osteoclastogenesis-related genes [ 7 , 8 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…DC-STAMP is known to play a role in cell–cell fusion and is one of the fusion mediator molecules directly regulated by NFATc1 [ 13 ]. Meanwhile, cathepsin K and TRAP are cysteine proteases secreted by osteoclasts that are responsible for decomposing matrix proteins during bone resorption [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ], we observed that the cell density has a major effect on the efficiency of osteoclastogenesis and measured the most efficient differentiation at an intermediate cell number. The fact that seeding density significantly impacts osteoclast differentiation has not only been observed for osteoclasts of human origin, but also for differentiation protocols based on murine/rat origin [ 26 , 27 ], thus indicating that cell density is a critical parameter in determining efficient osteoclastogenesis across various culture models. Another critical factor is the concentration of the two cytokines that reprogram monocytes towards osteoclasts, M-CSF and RANKL.…”
Section: Discussionmentioning
confidence: 99%
“…[ 113 ] During osteoclastic activation, both RANKL and CTSK are typically upregulated. [ 114 ] To distinguish between the M1, and M2/osteoclastic phenotype, macrophage morphology, the expression of RANKL and CTSK , and the presence of TRAP + staining were assessed. Our results show the cells remained mononucleated, with reduced levels of RANKL and CTSK on day 1, and became elongated and spindle‐shaped in a dose‐ and time‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%